Evaluation of the implementation of the gerakan literasi sekolah program using context, input, process, product, outcome at SMAN 1 Anjongan - Mahudi Mahudi; Maria Ulfah; Marinu Waruwu; Agung Hartoyo; Eni Rosnija (ARKA INSTITUTE, 2026)
This study evaluates the implementation of The Gerakan Literasi Sekolah at SMAN 1 Anjongan using the Context, Input, Process, Product, and Outcome (CIPPO) model. Employing aqualitative approach through interviews, observations, and documentation, data were collected from principals, teachers, the Tim Literasi Sekolah (TLS), and students through interviews, observations, questionnaires, and document analysis to evaluate the context, input, process, and product components of The Gerakan Literasi Sekolah (GLS). The findings indicate that in the context aspect, the GLS program has clear direction and policy foundations, though students' literacy skills remain low, and the Tim Literasi Sekolah legality needs strengthening. The input aspect reveals committed human resources and basic facilities, but limited funding and literacy training. The process aspect shows the 15-minute reading activity and journals are implemented, yet class consistency and teacher involvement as literacy models require improvement. The product aspect demonstrates tangible outputs such as student works, posters, and a more literate environment. Finally, outcome aspect shows positive impacts on students’ reading habits, the development of school literacy ecosystem, and efforts toward performance recognition through the school operational assistance program. Overall, the implementation of The Gerakan Literasi Sekolah is progressing well but still requires stronger institutional support, collaboration, and sustainability efforts.